2007
DOI: 10.1002/hbm.20372
|View full text |Cite
|
Sign up to set email alerts
|

Silent and continuous fMRI scanning differentially modulate activation in an auditory language comprehension task

Abstract: Sparse temporal acquisition schemes have been adopted to investigate the neural correlates of human audition using blood-oxygen-level dependent (BOLD) based functional magnetic resonance imaging (fMRI) devoid of ambient confounding acoustic scanner noise. These schemes have previously been extended to clustered-sparse temporal acquisition designs which record several subsequent BOLD contrast images in rapid succession in order to enhance temporal sampling efficiency. In the present study we demonstrate that an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
55
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 73 publications
4
55
1
Order By: Relevance
“…In addition to altering the response of the auditory cortex, 41 such studies have found that scanner noise can interact with stimuli to produce differential activity in, for example, the insula, cingulate gyrus and occipital cortex. 40,42,43 We can thus infer that scanner noise has an effect on these regions in the absence of stimuli, although further research on this front is required. Also of note is the possibility that MRI noise will corrupt EEG data acquired simultaneously during rest using combined fMRI-EEG.…”
Section: Auditory Noisementioning
confidence: 99%
“…In addition to altering the response of the auditory cortex, 41 such studies have found that scanner noise can interact with stimuli to produce differential activity in, for example, the insula, cingulate gyrus and occipital cortex. 40,42,43 We can thus infer that scanner noise has an effect on these regions in the absence of stimuli, although further research on this front is required. Also of note is the possibility that MRI noise will corrupt EEG data acquired simultaneously during rest using combined fMRI-EEG.…”
Section: Auditory Noisementioning
confidence: 99%
“…Scanner noise induces a BOLD response in auditory-related cortex areas during trials without a proper auditory stimulus. Most interestingly, this appears to happen differentially for the left and the right hemisphere (Herrmann et al 2000;Tamer et al 2009;Schmidt et al 2008) and in a nonlinear manner (Talavage and Edmister 2004). The degree of nonlinearity varies between left and right hemisphere (Hu et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of names exists to date for similar approaches: Edmister et al (1999) and Talavage et al (1999) presented ''clustered volume acquisition''; Hall et al (1999) called their approach ''sparse temporal sampling''; Eden et al (1999) published the ''behavior interleaved gradients technique''. In the present article we use the term ''sparse design'' for aforementioned approaches and ''clustered-sparse design'' for an extension of this design (Schmidt et al 2008;Zaehle et al 2007). ''Clustered volume acquisition'' refers to the temporal clustering of several slices within one volume and is not to be confused with the clustered-sparse protocol, which refers to the clustering of volumes within one trial.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations